Determination of fungi microorganisms on Amaranto seeds (Amaranthus spp.) by different analysis methods - Noelting, Maria C. (2004)
The absence of a methodology to analyze the micoflora in amaranth's seed, has motivated the performing of the present work. Seeds of two cultivars were sown (with and without disinfection process before sowing) on Petri dishes, some with "Blotter test" paper and others with five agarized culture media. All of them were placed in a chamber with 26 ºC± 2 and 16 h of photoperiod, and were incubated during seven days. After this period of time, the maximum number of different fungi genera developed on each substrate was registered, and the seed germination percentage was calculated. A total of fourteen genera of fungi (field and storage ones) were found, being Alternaria the most frequently isolated. In relation to the maximum number of fungi genera found, significant differences among the media analyzed (p>0,001) were detected, resulting the media APG, CZ and PCA the most effective ones. According to the disinfection treatment applied to the seeds before sowing, in general terms the fungi expansive growth was reduced. The germination percentage analysis revealed the presence of significant (p>0,001) interactions between amaranth cultivars and disinfection levels in four of the media analyzed, while in the remainder not significant interactions were registered.